To the Issue of Choosing the Criteria of Dynamics of Complex Physico-Chemikal Processes (Моделювання, керування та інформаційні технології, 2019)
On the basis of experimental studies, it was determined the capability to evaluate qualitatively and quantitatively the degree of arrhythmia of the carbon oxidation process, which determines the dynamics of the oxygen-converter metallurgical process.